“E-Matching Card” to Improve Cooperation and Cognitive Abilities Among Nursing Students - Elsye Maria Rosa; Sri Sundari; Eny Retna Ambarwati; Galuh Suryandari; Erna Rochmawati; Farid Suryanto (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
One of the learning models that can help students is the cooperative learning model (cooperative learning). Cooperative learning is a group learning method that makes students active in groups. They are expected to work together and discuss the tasks given by the lecturer. One type of cooperative learning model is making a match. Students make a matching learning model using learning cards can increase student activity so that this model is expected to be able to improve learning outcomes. The purpose of this research is to build a learning model using the student make a match approach’s learning cards to enhance nursing and midwifery students’ comprehension, interprofessional communication, and collaboration. The research method used was a pretest–posttest control group design. This research was conducted at one nursing education institution in Yogyakarta among fourth semester students totaling 60 within two months. The findings of this study are that learning using games creates an atmosphere that reduces student stress and facilitates student learning by increasing understanding, interprofessional communication, and collaboration among students (p-value=0.000). The conclusion of this study is that learning card games can improve students’ knowledge and teamwork/cooperation skills. Abstrak